From Snapshots of Practice to a Movie: Researching Long-Term Social Work and Child Protection by Getting as Close as Possible to Practice and Organisational Life. (5th November 2019) - Ferguson, Harry; Leigh, Jadwiga; Cooner, Tarsem Singh; Beddoe, Liz; Disney, Tom; Warwick, Lisa; Plumridge, Gillian
Abstract: Research into social work and child protection has begun to observe practice to find out what social workers actually do, however, no such ethnographic research has been done into long-term practice. This article outlines and analyses the methods used in a study of long-term social work and child protection practice. Researchers spent fifteen months embedded in two social work departments observing organisational practices, culture and staff supervision. We also regularly observed social worker's encounters with children and families in a sample of thirty cases for up to a year, doing up to twenty-one observations of practice in the same cases. Family members were also interviewed up to 3 times during that time. This article argues that a methodology that gets as close as possible to practitioners and managers as they are doing the work and that takes a longitudinal approach can provide deep insights into what social work practice is, how helpful relationships with service users are established and sustained over time, or not, and the influence of organisations. The challenges and ethical dilemmas involved in doing long-term research that gets so close to social work teams, casework and service users for up to a year are considered.